Comparative effect of supercritical carbon dioxide and high pressure processing on structural changes and activity loss of oxidoreductive enzymes. (January 2019) - Marszałek, Krystian; Doesburg, Paul; Starzonek, Szymon; Szczepańska, Justyna; Woźniak, Łukasz; Lorenzo, Jose Manuel; Skąpska, Sylwia; Rzoska, Sylwester; Barba, Francisco J.
Highlights: High pressure CO2 decreased enzymes activity as well as DC-conductivity. Polyphenol oxidases were more pressure and temperature resistant than peroxidases. CO2 affected enzyme activity under tenfold lower pressure than high pressure. Crystallization can be used for the structural changes determination of enzymes. Abstract: Due to the CO2 specific characteristics, it has been used as supercritical (Sc) fluid for several applications, including enzyme inactivation. The influence of Sc-CO2 (10–65 MPa/10–30 min/35–65 °C) on mushroom polyphenol oxidase (PPO) and horseradish peroxidase (POD) was evaluated and the results were compared with those found using high pressure processing (HPP) (200–900 MPa/5–45 °C/1–15 min). The free ion concentration was also studied to compare the enzymatic activity and changes in electrical conductivity. Additionally both enzymes, untreated or treated using either Sc-CO2 or HPP, were used as additives in the CuCl2 crystallization method. The resulting additive-specific CuCl2 patterns were characterized based on different structural features. Sc-CO2 was found to have a significant influence on PPO and POD activities, and an increased reduction in the residual activity of both enzymes was observed when the Sc-CO2 pressure was increased. However, PPO was more resistant to temperature and pressure than POD. The D-value calculated for POD was in the range of 38.3 and 592.0 min, and 60.6 and 291.5 min, for HPP and Sc-CO2 treatments, respectively; whereas for PPO varied from 103.1 to 284.3 min under HPP and from 83.4 to 303.0 min using the Sc-CO2 treatment. It can be concluded that the application of Sc-CO2 could be an effective tool for inactivating PPO and POD enzymes. Moreover, both enzymes and treatments could be differentiated significantly based on the resulting CuCl2 crystallization patterns.